Kajian Ketersediaan Dan Kebutuhan Air Baku Dengan Pemodelan Ihacres Di Daerah Aliran Sungai Tapung Kiri - Mashuri Mashuri; Manyuk Fauzi; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The demand of raw water in Kampar Districts is increasing in step with population growth. At this time, the water supply system is regulated by PDAM Tirta Kampar what still have problem to service coverage. Especially Tapung Sub-District has not been served. Therefore, the existence of the Tapung Kiri River is expected to be a solution to overcome these problems. Thisstudy use IHACRES for rainfall - runoff modeling, which in the calibration stage reach Nash- Sutcliffe effectiveness value of 0.630. Overall, this model provides an understanding that thesuccess obtained on the calibration stage does not guarantee success in the verification stage. Analysis of water availability is done to analyze the realable discharge river (Q90%) based onaverage annual the discharge resulting realable discharge occurred in 2000. The greatest realable discharge occured in October amounted to 93.75 m3/sec, and the smallest in Maretamounted to 43,69 m3/sec. Analysis of water demand is forecasted to the population growth of up to 22 years and produce raw water demand total with forecasts early of the year (2013) of 0.109 m3/sec and the end forecasts of the year (2035) of 0.264 m3/sec.Keyword : Tapung Kiri River, IHACRES model, Availability Water, Population Forecasts, Water Supply